Case study on dairy value chain in China - Hongmin, Dong; Sha, Wei; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Hongmin Dong and Sha Wei, Chinese Academy of Agricultural Sciences (CAAS), on 28 June 2021 at the Asian Development Bank (ADB) Webinar on Sustainable Protein Case Study: Outputs and Synthesis of Results.